2005
DOI: 10.1136/aim.23.2.47
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Insomnia in Pregnancy – a Prospective, Quasi-Randomised, Controlled Study

Abstract: Objective This study was undertaken to test the effects of acupuncture on insomnia in a group of pregnant women under real life conditions, and to compare the results with a group of patients undergoing conventional treatment alone (sleep hygiene). Methods A total of 30 conventionally treated pregnant women were allocated at random into groups with or without acupuncture. Seventeen patients formed the study group and 13 the control group. The pregnant women scored the severity of insomnia using a Numerical Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Only one study (5.0%)19 21 provided a definition of AEs. Eight out of 20 studies (40.0%) reported the method used to collect AEs: three studies used direct questioning,18 20 26 34 two used patient diaries,28 33 one used a questionnaire,36 Vas et al 4 used patient case notes, direct questioning and a questionnaire and Smith et al 19 21 used direct questioning and patient case notes. Ninety percent of studies reported the type and frequency of AEs in each group but none stated the severity; only Elden et al 18 20 assessed the severity of some but not all of the reported AEs.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study (5.0%)19 21 provided a definition of AEs. Eight out of 20 studies (40.0%) reported the method used to collect AEs: three studies used direct questioning,18 20 26 34 two used patient diaries,28 33 one used a questionnaire,36 Vas et al 4 used patient case notes, direct questioning and a questionnaire and Smith et al 19 21 used direct questioning and patient case notes. Ninety percent of studies reported the type and frequency of AEs in each group but none stated the severity; only Elden et al 18 20 assessed the severity of some but not all of the reported AEs.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, 108 identified reports 7–114qualified for review and analysis.They encompass a wide range of condi‐tions/symptoms, including: osteoarthritis/knee pain, migraine, low back pain, pelvic pain, hot flashes, labor pain and labor initiation, analgesic and sedative ef‐fects in surgery/cancer pain, tension‐type headache, shoulder/arm pain, embryo transfer, irritable bowel syndrome, allergic rhinitis, depression, fibromyalgia, myofascial pain, insomnia, inflammatory breast in lactating women, stroke reha‐bilitation, anxiety, nausea and vomiting, dry eyes, hypertension, post‐traumatic stress disorder (PTSD), recurrent cystitis, psychogenic erectile dysfunction, chronic post‐stroke leg spasticity, overactive bladder, refractory heartburn, rheuma‐toid arthritis, disabling breathlessness, impingement syndrome, cervical spondy‐losis, chronic obstructive pulmonary disease (COPD), diabetic bladder dysfunc‐tion, balance function after stoke. The sample size of those articles varied from 16 to over 3000.…”
Section: Resultsmentioning
confidence: 99%
“…A combination of usual sleep hygiene techniques such as adjusting fluid intake to reduce nycturia, pillow support to manage physical discomfort, and favorable environment [4] can be recommended. More rarely, among women experiencing severe insomnia failing to respond to usual sleep hygiene techniques, behavioral therapies (stimulus control therapy, relaxation techniques) [19], acupuncture [20], phytotherapy [21], and exceptionally, pharmacologic therapy through hypnotic agents [4] can be attempted in order to alleviate insomnia.…”
Section: Discussionmentioning
confidence: 99%